Identify the effectiveness of a training program based on remote supervision in developing some of the electronic supervision competencies it among the educational supervisors in the kindergarten stage in the city of Makkah - Al-Saigh, Ohood Khaled; Babtain, Hoda Muhammad (Journal of Curriculum and Teaching Methodology, 2024)
The current study aimed to identify the effectiveness of a training program based on remote supervision in developing some of the electronic supervision competencies it among the educational supervisors in the kindergarten stage in the city of Makkah. To achieve that goal, the study followed the descriptive approach, and the experimental approach based on the one-group pretest-posttest quasi-experimental design. The training program was designed, and the study tools which included: a cognitive test consisting of (20) questions; a performance evaluation card consisting of (18) items distributed on the three axes of electronic supervisory competencies (e-learning competencies, distance training competencies, and the competencies of electronic evaluation), the tools were distributed to the study sample consisting of (23) educational supervisors in kindergarten level in Makkah. Based on a number of statistical methods, the study reached the following results: there were numerous statistically significant differences (α
Keywords: training program; remote supervision; electronic supervisory competencies